Subcutaneous fat necrosis of the newborn with transient ischemia of a lower limb. - Laforgia, N.; Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
A baby girl was born full term with Cesarean section. The history showed tracing abnormalities and liquid stained with meconium. She was hospitalized in the Intensive Care Unit due to whitening of the right lower limb in absence of umbilical catheterism. Color ultrasonography unveiled a transient occlusion of the right common femoral artery, which regressed shortly after. During the examination hard, not painful, infiltrated plaques of the subcutaneous fat were noted bilaterally on the root of the upper and lower limbs in absence of skin signs (Fig. 1, 2, 3). The raised ESR and C-reactive protein led to an antibiotic treatment. 3 days later, the unchanged clinical features led to perform a biopsy. The latter showed in the subcutaneous fat an infiltrate of histiocytes and giant cells, with needle-shaped, radially arranged crystals inside the fat cells (Fig. 4 and box), leading to the final diagnosis of subcutaneous fat necrosis of the newborn.